2009
DOI: 10.1007/s12160-009-9111-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and Physical Health: A Meta-analytic Review

Abstract: Background-Prior research links optimism to physical health, but the strength of the association has not been systematically evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
503
5
42

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(579 citation statements)
references
References 100 publications
29
503
5
42
Order By: Relevance
“…In addition to examining the association between PPWB and deteriorative processes, we examine the association between PPWB and restorative processes that may protect against CVD. This is consistent with the American Heart Association's recent emphasis on ideal cardiovascular health, which is defined by more than just the absence of risk factors (Lloyd-Jones et al, 2010).Furthermore, previous reviews have primarily focused on positive affect (for an exception, see Rasmussen, Scheier, & Greenhouse, 2009). In contrast, we take a broad perspective on PPWB and consider a wide range of positive constructs that we classify by the dominant theoretical approaches to well-being.…”
supporting
confidence: 74%
“…In addition to examining the association between PPWB and deteriorative processes, we examine the association between PPWB and restorative processes that may protect against CVD. This is consistent with the American Heart Association's recent emphasis on ideal cardiovascular health, which is defined by more than just the absence of risk factors (Lloyd-Jones et al, 2010).Furthermore, previous reviews have primarily focused on positive affect (for an exception, see Rasmussen, Scheier, & Greenhouse, 2009). In contrast, we take a broad perspective on PPWB and consider a wide range of positive constructs that we classify by the dominant theoretical approaches to well-being.…”
supporting
confidence: 74%
“…For example, positive affect, independent of negative affect, has been demonstrated to be inversely related to the risk of incident stroke (Ostir, Markides, Peek, & Goodwin, 2001), 10-year incidence of coronary heart disease (Davidson, Mostofsky, & Whang, 2010), mortality in medical in-patients (Scherer & Hermann-Lingen, 2009), and mortality in diabetic patients (Moskowitz, Epel, & Acree, 2008). These findings are also consistent with research demonstrating a positive relationship between optimism and favorable subjective health (Rasmussen & Wallio, 2008;Rasmussen, Scheier, & Greenhouse, 2009), although it should be noted that the optimism differs somewhat from positive affect in that the former refers more to favorable outcome expectancies (Scheier & Carver, 1985). However, negative and positive affect were not identical in their respective associations with the physical disorders.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have established positive relations between optimism and physical and mental health outcomes (Segerstrom et al, 1998;Taylor et al, 2000;Rasmussen et al, 2009). For example, Segerstrom et al (1998) found that dispositional and situational optimism was related to more positive mood ratings and more positive immune parameters in college students.…”
Section: Introductionmentioning
confidence: 96%